REVOLUSI KOMUNIKASI DAN PERUBAHAN SOSIAL (DAMPAK PANDEMI COVID-19 PADA MAHASISWA) - Fauzi Eka Putra (KAREBA : Jurnal Ilmu Komunikasi, 2020)
The purpose of this study is to analyze the communication revolution and the social changes that impact the Covid-19 pandemic on society. This research uses the theory of Social Change and Modernization. The informants in the study were students of the Islamic Broadcasting Communication Department of IAIN Bukittinggi. The research method used is a qualitative research method with a phenomenological approach study. The results showed that the communication revolution that is happening right now Students who are economically capable, can communicate well with their Lecturers using one of the modernization products namely information technology (smartphone) with applications such as WAG, Google Classroom, Meetgoogle, Zoom and others. While students who are economically incapable, they cannot communicate with their lecturers in the learning process at home. The perceived obstacle for economically disadvantaged students is the financial constraints of buying a smartphone as a means of communicating with their lecturers, pulses and data packages to contact the lecturer, some using their parents' cellphones or relatives. While students who are economically capable, the obstacle in this case is that they often use communication tools, they more often abuse these communication tools for other purposes such as being used to play games, tiktok, social media, youtube and others especially if their parents fill out data packages unlimited. Keywords: Communication Revolution, Social Change, Covid-19